The effects of ART on the dynamics of lipid profiles in Chinese Han HIV-infected patients: comparison between NRTI/NNRTI and NRTI/INSTI - Liu, Shengnan; Wei, Baozhu; Liang, Wei; Chen, Tielong; Deng, Liping; Zhao, Min; Wan, Jing (Frontiers in Public Health, 2023)
Introduction: This article aimed to compare the prevalence of dyslipidemia and determine risk factors associated with lipid levels in a cohort of HIV-infected patients receiving two different ART regimens, NRTI/NNRTI and NRTI/INSTI. Methods: This longitudinal study analyzed 633 HIV-infected patients with complete blood lipid profile records for at least 1 year at the ART clinic of Zhongnan Hospital of Wuhan University, China, from June 2018 to March 2021. Demographic and clinical data, including age, gender, body weight, height, current/former/non-smoker, current drinker, diabetes mellitus, hypertension, were extracted from electronic medical records. Laboratory tests included hematology, total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), Lipoprotein(a) and CD4 cell count. The observation duration of this study was a maximum of 33 months. Data comparisons were performed using the Chi-square test, Student’s t-test and Mann-Whitney U Test. Generalized linear mixed-effects model (GLMM) and p-value <0.05 were used to determine factors associated with serum lipid profiles. Results: In this study, the effect of the NNRTIs group on the lipid profile over time was mainly an increase in TC and HDL-C, while a decrease in TC/HDL-C and LDL/HDL-C. However, the INSTIs group had higher mean TC and lower HDL-C compared to the NNRTIs group, with significantly increased levels of TC, TG, HDL-C, and LDL-C. Dyslipidemia, defined as hypercholesterolemia, hypertriglyceridemia, and low HDL-C, was more prevalent in the INSTIs group, with a higher risk of developing hypertriglyceridemia and a higher TC/HDL-C ratio compared to the NNRTIs group. GLMM analysis suggested significantly higher TG values in the INSTIs group (estimated 0.36[0.10, 0.63], SE 0.14, p=0.008) compared to the NNRTIs group, even after adjusting for other covariates. In addition, GLMM analysis also showed that age, gender, BMI, CD4 count, and ART duration were associated with dyslipidemia. Conclusions: In conclusion, treatment with both commonly-used ART regimens can increase the mean values of lipid profiles and the risk of dyslipidemia. The findings indicated that TG values were significantly higher in the INSTIs group than in HIV-infected patients receiving the NNRTIs regimens. Longitudinal TG values are independently associated with the clinical types of ART regimens.